Dispersion of Graphene Nanoplatelets in Polylactic Acid with the Aid of a Zwitterionic Surfactant: Evaluation of the Shape Memory Behavior. (2nd July 2016) - Keramati, Mohsen; Ghasemi, Ismaeil; Karrabi, Mohammad; Azizi, Hamed; Sabzi, Mohammad
ABSTRACT: Developments in the dispersion of graphene nanoplatelets in polylactic acid were achieved with the aid of a zwitterionic surfactant. The graphene nanoplatelet surface modification was tracked by Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray diffraction, and elemental analysis. Different amounts of graphene nanoplatelets and surface-modified graphene nanoplatelets (3 and 6 phr) were used to prepare the polylactic acid nanocomposite through a solvent-mixing method. It was found that surface-modified graphene nanoplatelets were exfoliated and homogeneously dispersed in the polylactic acid matrix. Better dispersion of surface-modified graphene nanoplatelets compared with graphene nanoplatelets was due to enhancement of the polymer–graphene interaction induced by the zwitterionic surfactant. The shape memory properties of nanocomposites were evaluated using thermomechanical analysis. The obtained results revealed that the shape memory performance of nanocomposite samples was affected by the degree of dispersion. Higher shape recovery of nanocomposite samples in comparison with that of neat polylactic acid was obtained, which originated from their higher elastic glassy modulus. Up to 91% shape recovery was determined in nanocomposite samples containing surface-modified graphene nanoplatelets, which was attributed to the good dispersion of surface-modified graphene nanoplatelets in the polylactic acid matrix. GRAPHICAL ABSTRACT: